Ex-vivo nephron-sparing surgery and autotransplantation for renal tumours: Revisited - Abraham, George P; Siddaiah, Avinash T; Ramaswami, Krishnamohan; George, Datson; Das, Krishanu (Canadian Urological Association Journal, 2014)
Introduction: We studied the feasibility of ex-vivo nephron-sparing surgery and autotransplantation for complex renal tumours. We also studied the role of laparoscopy in these situations. Methods: All patients who underwent renal autotransplantation for renal tumour at our centre were included in this retrospective study. Patient profiles were recorded in detail. Operative and postoperative details were also recorded. Results: Our series includes 3 patients. Two patients had complex renal cell carcinoma and 1 patient had bilateral large angiomyolipoma. In the first 2 patients, laparoscopic approach was used for nephrectomy. Operative time for case 1, 2 and 3 was 5.5, 4.5, 8 (right side) and 6 (left side) hours, respectively. Cold ischemia time was 110, 90, 150 and 125 minutes, respectively. One patient required temporary postoperative hemodialysis. Conclusion: Ex-vivo nephron-sparing surgery and autotransplantation still remain a viable option for complex renal tumours. It offers satisfactory renal functional outcome with acceptable morbidity. The laparoscopic approach should be used whenever possible to reduce morbidity.